PAULO AUGUSTO E A POESIA HOMOERÓTICA: TRANSGRESSÃO E PIONEIRISMO EM FALO (Muitas Vozes, 2024)
The 20th century was marked by the ascension of the social movements' reclamation of visibility over oppressed bodies. This change had extreme importance so these bodies could have the presence they have nowadays in different sectors. Making way, for instance, to their literature representations. However, In the Brazilian scene, queer literature's place is still uncertain and it's clear that  many authors and texts stay at its borders. This way, through a work of rescue, this research offers to recover aspects from the work “Falo” (phallus), written by Paulo Augusto, Brazilian writer who published his first book during the 70's in an assertive, acid tone in the middle of a militar dictatorship. As theoretical reference, this research has names such as Judith Butler, Michel Foucault, Guacira Lopes Louro, Richard Miskolchi. In this context, using Queer Theory's aspects (as an example/base), this research went through three poems ("Avant-premiere", "Vae Victis" and  "Estatuto"). Looking how these texts deal with subjects like social impositions of a gender, the repression over dissident bodies for a cisheteronormative standard of sex/gender and the marginal position these bodies. This way, this research intends to give visibility to an author who, although being a pioneer on homoerotic poetry's exploration, ended up being erased by critics.